STUDENTS’ PERCEPTION OF THE USE OF MOBILE ASSISTED LANGUAGE LEARNING (MALL) TO LEARN ENGLISH - Arilia Triyoga; Afif Chandra Rizaldy; Rifky Dora Wijayati (Universitas Muhammadiyah Makassar, 2023)
Computer Assisted Language Learning (CALL) is no longer popular among language learners due to its impractical comparison to Mobile Assisted Language Learning (MALL). MALL is a language learning tool that can assist students in expanding their learning possibilities and reshaping their language learning approach. This research aims to analyze the students’ perception of using MALL to learn English. This research was conducted using mixed methods and closed-ended questionnaires using the Likert scale of 1 to 6 to find out student perceptions of the use of MALL on the Perceived Usefulness (PU) and Perceived Ease of Use (PEoU) to gather the data. An interview was also conducted to get a more comprehensive finding. The respondent showed that they had a positive perception of the use of MALL to learn English. They agreed on the potential of MALL as a practical approach to learning English. Meanwhile, the interview session revealed that the students had drawbacks in using MALL to learn English, such as networking, technical problems on camera, and vocabulary difficulties on certain websites. Still, the students can maximize their use of it.